Preliminary Study of Difenoconazole Residues in Rice Paddy Watersheds. - Ab. Latiff, Khalidah; Abu Bakar, Nor Kartini; Md Isa, Nurzawani (Malaysian Journal of Science, 2010)
Pesticide application to rice paddies may affect the quality of environmental resources such as groundwater and surface water. The distribution of residues of difenoconazole (an effective fungicide) used was monitored in the network of surface water bodies surrounding the main rice production area in Tajar, Kedah. The location monitoring sites was based on the potential risk for contamination of difenoconazole. The analysis was done by using liquid-liquid extraction (LLE) and detected by gas chromatography-mass spectrometer (GC-MS). Limit of detection (LOD) was 0.0618 ppm. Recoveries of difenoconazole at spiking level of 400 ppm, 8 ppm and 0.5 ppm were between 93% - 106%.